Properties of Maxentropic DNA Synthesis Codes - Kees Schouhamer Immink; Jos H. Weber; Kui Cai (Entropy)
Low-weight codes have been proposed for efficiently synthesizing deoxyribonucleic acid (DNA) for massive data storage, where a multiple of DNA strands are synthesized in parallel. We report on the redundancy and information rate of maxentropic low-weight codes for asymptotically large codeword length. We compare the performance of low-complexity nibble replacement (NR) codes, which are designed to minimize the synthesis time, with the performance of maxentropic low-weight codes. Finally, the asymptotic redundancy and information rate of codes with a runlength limitation are investigated.